Between the world of economics and the world of physical sciences there would be a link that is anything but hypothetical - Cossiga, Giovanni Antonio (Advances in Social Sciences Research Journal, 2021)
The compatibility between humanity and nature should be related to a trend that would lead us hopefully in a short time to the full neutrality between man and the planet we all live on. Along this trend, essentially due to the cooperation and help of science and knowledge, the humankind is able to collect news and information on the level of pollution we produce, not to be exceeded. Individually, the information on the pollution degree received from nature comes to us through the monetary system. Therefore, the community is warned that we are approaching a limit not to be exceeded in creating pollution inside the environment and the warning comes through the nominal price system, that is through inflation and deflation. These two are nothing more than messages, like ectoplasms, that is a sort of symbols taking shape due to the economic instability and, once inside the economic environment, they lose contact with the economic entourage. Nor could it be otherwise, because their task is for information purposes only, and they must create within the community the loss of confidence in the economic outlook. Due to this loss of trust, the economy slows down and takes a pause in favor of the environment quality, which improves thanks to the reduced economic activity. It’s a sort of alert system with the same message function both for inflation and deflation. However, their fate is anyway different not for a natural reason but for the different response given by monetary policy upon arrival of inflation or deflation. In the case of inflation, the monetary policy response is the symmetry between nominal price increases and interest rates. This increase in rates is producing a cycle retreat that is consistent with the request for a pause of the natural system. While in the case of deflation, the symmetry between the decline in nominal prices and interest rates is in contrast with the economic system demanding for a pause. This potential opposition can cause some anomalies in the wealth and income distribution.